2005
DOI: 10.1038/nature04021
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for CoREST in nucleosomal histone 3 lysine 4 demethylation

Abstract: We have previously described a multiprotein complex termed the BHC or BRAF-HDAC complex, which is required for the repression of neuronal-specific genes. We have shown that the BHC complex is recruited by a neuronal silencer, REST (RE1-silencing transcription factor), and mediates the repression of REST-responsive genes. BHC is a multiprotein complex consisting of two enzymatic activities: a histone deacetylase (HDAC1 or 2) and a recently described histone demethylase (BHC110, also known as LSD1 or AOF2). Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
690
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 707 publications
(720 citation statements)
references
References 22 publications
28
690
0
2
Order By: Relevance
“…Interaction of retinoid receptors with b-catenin at the Id2 gene WRE presumably leads to recruitment of repressor complexes containing histone deacetylase and demethylase activities. Indeed, we were able to detect a retinoid-dependent recruitment to WRE in the Id2 gene promoter of LSD1 demethylase (Figure 5a), shown to be essential for histone H3 Lys-4 demethylation (Shi et al, 2004;Lee et al, 2005). As histone demethylases and deacetylases are believed to be present in non-related regulatory complexes, the observed pattern of histone modification at the Id2 gene implies sequential or independent recruitment to the WRE of different chromatin remodeling complexes.…”
Section: Discussionmentioning
confidence: 85%
“…Interaction of retinoid receptors with b-catenin at the Id2 gene WRE presumably leads to recruitment of repressor complexes containing histone deacetylase and demethylase activities. Indeed, we were able to detect a retinoid-dependent recruitment to WRE in the Id2 gene promoter of LSD1 demethylase (Figure 5a), shown to be essential for histone H3 Lys-4 demethylation (Shi et al, 2004;Lee et al, 2005). As histone demethylases and deacetylases are believed to be present in non-related regulatory complexes, the observed pattern of histone modification at the Id2 gene implies sequential or independent recruitment to the WRE of different chromatin remodeling complexes.…”
Section: Discussionmentioning
confidence: 85%
“…HDAC1 and HDAC2 lack a DNA-binding domain, as do all deacetylases, and execute their function by interacting with transcription factors as either homo-or heterodimers, or being part of multi-component repressor complexes. 8,9 The best characterized HDAC1/2-containing complexes in mammals are the SIN3 co-repressor complex, 23 nucleosome remodeling and deacetylase (NuRD) complex, 24 CoREST complex, 25 Nanog and Oct4 (POU5F1)-associated deacetylase complex that is specifically found in embryonic stem (ES) cells, 26 and PRC2 complex. 27 The ubiquitous expression, high deacetylase activity toward common substrates and high homology between HDAC1 and HDAC2 suggest that each could compensate for loss of function of the other.…”
Section: Structure and Complexes Of Mammalian Hdac1 And Hdac2mentioning
confidence: 99%
“…There are many examples of N(itrogen)-methylations (of arginine, lysine, glutamine, asparagine, histidine residues, and the amino group at the N terminus) in the cell. While it is not certain that all N-methylations are reversible, recent discoveries showed that a human nuclear peptidyl arginine deiminase, PAD4, antagonizes methylation on the arginine residues by converting arginine to citrulline [92][93][94] (Figure 5); a human nuclear amine oxidases, LSD1, functions as a histone di/mono-methyl-lysine demethylase via an oxidation reaction [95][96][97]; and JmjC domain-containing hydroxylase-like proteins are able to demethylate mono-, di-, or tri-methylated lysines [98,99], which was first proposed for S. pombe Epe1 [100].…”
Section: Demethylation By Oxidation or Hydroxylationmentioning
confidence: 99%
“…Within these complexes, REST (RE1-silencing transcription factor) corepressor CoREST enables LSD1 to demethylate nucleosomes [96,97], while BHC80 (BRAF-HDAC complex) inhibits LSD1 activity [96]. The LSD1 polypeptide chain can be divided into several structural/ functional regions (Figure 6a): the N-terminal putative nuclear localization signal, followed by a SWIRM (Swi3p, Rsc8p, and Moira) domain (Figure 6b; [101])-found in several nucleosome-interacting proteins -and a monoamine oxidase domain -capable of demethylating lysines in an flavin-dependent manner [102].…”
Section: Lsd1mentioning
confidence: 99%